ANALISIS KEKERABATAN GENETIK TANAMAN PADI (Oryza sativa L.) DI KABUPATEN KAMPAR DENGAN MENGGUNAKAN PENANDA Random Amplified Polymorphic DNA (RAPD) - Rita Elfianis; Joko Warino; Rosmaina Rosmaina; Suherman Suherman; Zulfahmi Zulfahmi (Jurnal Agroteknologi, 2021)
Rice is a cereal crop that belongs to the graminae family of high economic value, and is the main food for more than a portion of the world's population. This study aims to determine the relationship genetic of rice in Kampar by RAPD marker. Eight genotypes of rice from district in Kampar were amplified using eight primers (OPA 5, OPB 7, OPC 19, OPD 2, OPD 3, OPD 8, OPD 11, and OPD 13). The analysis of molecular data was performed by using NTSys pc -2.02 and GenAlex 6.1 . The results of the amplification of rice produced 48 loci with DNA band sizes obtained ranging from 350-1700 bp. The average percentage of polymorphic loci of the eight primers was 49.80%, where the highest percentage of polymorphic loci produced by OPA-7 primer was 75%, while the lowest polymorphic locus percentage was observed in OPD-13 primer which was 14.28%. The value of genetic distance between rice from Kampar in this study is in the range of 0.06 - 0.37. At a genetic distance of 0.79, rice plants can be grouped into two groups, namely the first group consisting of sokan and coku. The second group consisted of suntiong, korean , cupak putio, kuniong, jangguik, and cupak tenggi. The results of this study are expected to be taken into consideration in developing rice breeding strategies in the future.